2008
DOI: 10.1590/s1516-89132008000600015
|View full text |Cite
|
Sign up to set email alerts
|

Predacious activity of Ants (Hymenoptera: Formicidae) in conventional and in No-till agriculture systems

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…are ecologically diverse, and it also collects seeds, are omnivorous, predatory and mutualistic in associations with plants (Soares et al, 1998). The higher frequency of ants in a no-till area than in conventional crops suggests that the organic matter in this system increases the populations of Termitidae (Lange et al, 2008).…”
Section: Resultsmentioning
confidence: 94%
“…are ecologically diverse, and it also collects seeds, are omnivorous, predatory and mutualistic in associations with plants (Soares et al, 1998). The higher frequency of ants in a no-till area than in conventional crops suggests that the organic matter in this system increases the populations of Termitidae (Lange et al, 2008).…”
Section: Resultsmentioning
confidence: 94%
“…According to Bolton (1995), Pheidole is between the 10 richer genera in number of Formicidae species. This high species richness added to the fact that the nests have many individuals, make this genus ubiquitous in natural or disturbed environments (see ANDERSEN, 2000;BROWN Jr., 2000;WARD, 2000;LANGE et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…According to Hölldobler and Wilson (1990), this group is the largest subfamily of Formicidae in number of species and variety of food and nesting habits, with wide adaptation to disturbed environments. Furthermore, many authors have shown that most Myrmicinae species are aggressive and they have efficient and massive recruitment, being of ten sampled in agrosystems (Castro & Queiroz, 1987;Perfecto, 1991;Lange et al, 2008;Falcão et al,2015).They are considered to be effective agents in the biological control of pests in crops (see Fernandes et al,1994Fernandes et al, , 2012.…”
Section: Community Compositionmentioning
confidence: 99%
“…In addition to their role as bioindicators of environmental change, most ant species are efficient predators of other insects, contributing to pest control in crops (Perfecto, 1991;Agarwal et al, 2007;Rico-Gray & Oliveira, 2007;Lange et al, 2008). According to Booij and Noorlander (1992), ants, beetles and spiders are the most effective generalist predators in agrosystems.…”
mentioning
confidence: 99%
See 1 more Smart Citation